Pengembangan Model Alat Stick Hockey Untuk Latihan Pemain Pemula Hockey (Department of Physical Education, Sport, Health and Recreation, 2016)
Background issues that hamper the development of hockey in Central Java due to the lack ofmeans of stick that is expensive and so difficult to get it. The focus of this research problemis to design products hockey stick model development tool for training novice players and testproducts hockey stick model development tool for training novice players.The approach usedin this research is the Research and Development. Phase of the study include preliminary research,design modeling, model development testing procedures, expert Judgment, small-scaletrials, trials broad scale. The subject of this study is Mts Miftahussalam 1 Wonosalam Demak.Hockey expert of experts and specialists timber expert. The data analysis phase of fieldwork and data analysis stage include observation, observation, interviews, documentationand effectiveness testing of products, expert judgment hockey expert of experts and specialiststimber expert.The results of this study are the product hockey stick for beginner hockey playerstraining in Mts Miftahussalam 1 Wonosalam.PANDAWA hockey stick product can be usedas a means of practicing basic techniques for beginner hockey players, hockey stick PANDAWAproduct can be used as a training tool in improving the ability of the basic techniques ofplaying hockey, hockey stick PANDAWA product can be used as a means of playing hockeyfor the novice player.